2022
DOI: 10.3233/wor-210994
|View full text |Cite
|
Sign up to set email alerts
|

Teachers feeling the burden of COVID-19: Impact on well-being, stress, and burnout

Abstract: BACKGROUND: Teachers have had to deal with many of the negative aspects of COVID-19 over the past year. The demands associated with the sudden requirement to teach remotely, and later having to manage hybrid (both in person and online) learning may be having adverse effects on the mental and physical health of teachers. OBJECTIVE: To determine whether COVID-19 continued to impact teacher stress, burnout, and wellbeing a year into the pandemic. METHODS: An online survey was sent out to 5300 teachers in public a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
56
2
8

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(72 citation statements)
references
References 29 publications
6
56
2
8
Order By: Relevance
“…This study contributes to current literature on the effects of the COVID-19 pandemic on teachers, where most studies have focused on the psychological stress among teachers [ 11 , 25 ] and/or the impact of remote learning on education [ 10 , 26 ]. Fukuda and Fukuda (2022) found that one of the contributions to educators’ stress included infection prevention [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study contributes to current literature on the effects of the COVID-19 pandemic on teachers, where most studies have focused on the psychological stress among teachers [ 11 , 25 ] and/or the impact of remote learning on education [ 10 , 26 ]. Fukuda and Fukuda (2022) found that one of the contributions to educators’ stress included infection prevention [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…The stress and organizational challenges and feelings of burnout among teachers internationally are widely recognized [ 9 , 10 , 11 , 12 , 13 ]. In the U.S., specifically, the real-world challenges for teachers in implementing CDC guidance for K-12 schools are not well characterized.…”
Section: Introductionmentioning
confidence: 99%
“…In a study examining the impact of COVID-19 on well-being, 72% of teachers surveyed reported feeling very or extremely stressed, and 57% felt very or extremely burned out [4]. Poor office ergonomics and discomfort have been identified as major contributing factors to the increase in stress [5]; a study which examined the ergonomics of virtual offices conducted an 8-month follow-up survey and found that faculty and staff working with just a laptop continued to report high levels of body discomfort [6]. Additional contributing stress factors unique to remote work have been identified as increased workload, peer interaction, organization climate, and role ambiguity [7].…”
Section: Introductionmentioning
confidence: 99%
“…In a survey conducted in Greece in 2020, changes were found in teachers' mind and body related to COVID-19, and results showed that many teachers felt anxious due to the COVID-19 pandemic [28]. Compared with before the pandemic, mental changes were associated with decreased QOL [29], increased stress [30], and increased burnout [30,31]. There are some reports that female faculty are more likely to develop fear, depression, stress disorders and depression in comparison of sex [32].…”
Section: Introductionmentioning
confidence: 99%